Sprachstil Auf Der Onlineshop www.gambio.de - PUTRI R, DINDA (LATERNE, 2013)
Language style is a way of using language. Various style usually appears in one advertisement. www.gambio.de is an online shop in Germany. Gambio sells software for online shop. There are so many online shops that use software from Gambio. On the reference page of Gambio there are many descriptions of the online shop. These descriptions are advertising on their online shop. In one advertisement, there are more than one style. Therefore carried out research about the Gambio’s language style. Problems in this study is "What type of style that is used on the online shop www.gambio.de?" And "what type of language style of the most widely used on the online shop www.gambio.de?" This study has two purposes, namely, "to mention the types of language style used on the online shop www.gambio.de" and "to mention the type of language style most widely used on the online shop www.gambio.de." Qualitative descriptive methods used in this study. Five descriptions of the online shop on a reference page of Gambio is the datas research. The analysis of this study used the theory of the types of language style Gorys Keraf and Joachim Schmid. In this study discovered a lot of style, such as hyperbole, metaphor, metominia, Fremdwort, Neologismus and others. Language style is the most widely used hyperbole and Fremdwort. The advertisements are very varied. But there is a typo in the two online shop, and Prestige-tuning.de CEPURA.de. The author should be more careful in the next advertisement.